The Philosophical, Political and Religious Roots of Touch Exhibitions in 20th Century British Museums - Hayhoe, Simon (Disability Studies Quarterly, 2013)
This article examines the philosophical, social and cultural roots of touch exhibitions in British museums during the Twentieth Century. The theory and practice of these exhibitions was influenced more by cultural tradition, and political and social guidance, than by the needs of the majority of people with disabilities of sight. In particular, a theory of the use of touch was derived from pedagogies developed in schools for the blind, which were themselves influenced by a philosophy of enlightenment from the seventeenth and eighteenth centuries. This pedagogical and theoretical approach does not serve people with disabilities of sight well. The study concludes that touch should only be used as one of a number of multimodal approaches to museum access, and people with disabilities of sight should be considered according to their individual needs. Keywords: blindness, disabilities of sight, touch, tactile, museums, galleries, exhibitions, access, enlightenment, philosophy, schools for the blind, pedagogy